BACK -DATED AGREEMENTS ACCORDING TO AGREEMENT LAW IN DELI SERDANG - Albin Fajzri (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
The legal basis of a valid contract according to the Civil Code is regulated in Article 1338 of the Civil Code, namely that all formal contracts apply as law for the parties thereto. From this article it can be concluded that there is a principle of freedom of contract, but this freedom is limited by the law of coercion, so that the contracting parties must submit to the law of coercion. The legal consequences of a previous contract for the parties to the contract can be terminated by one of the parties who submits a request for cancellation, a demand for a refund or even a claim for compensation if misstatements and errors are found in the contract and the backdated date. The validity and date of withdrawal of physical evidence of the contract, it is necessary to first examine the conditions for the validity of the contract, which must meet the prerequisites (agreement of the parties), although Article 1321 of the Civil Code emphasizes the validity of the contract itself, which must not be the result of error, coercion or fraud.